Implementasi Pasal 83 Undang-Undang Nomor 13 Tahun 2003 Tentang Hak Menyusui Pekerja Perempuan Selama Waktu Kerja Analisis Perilaku pada Institusi Kesehatan dan Non Kesehatan di Kota Semarang - Nurjanah, Nurjanah; Rachmani, Enny (Jurnal Promosi Kesehatan Indonesia, 2008)
Background : Role of working woman in the work activity is more important nowadays. Working woman come to mainstream in much industry. But, working woman was treated discriminatively because of her role both as mother and employee. In Indonesia, woman rights as labor have been arranged in Labors Law number No. 13 year 2003 : worker woman who have child that still have breastfed have to give opportunity to breastfeed her child if must be done during work time ( Section 83 ). But this working woman rights is often be blamed cause unproductive by company. So that, baby do not get exclusive breastfeeding in 6 months although breast milk is the best food for babies. Breast milk contents all of nutrition for optimal baby growth, and vitamins for intelligence and immunity.Method : The objectives of this research were identifying predisposing factors include: mother’s knowledge about benefit of breast milk, mother’s attitude about breastfeeding, and believes about breast milk compared to formula; identifying enabling factor include : availability of facilitiesand time supporting breastfeeding behavior; identifying reinforcing factors include: implementing breastfeeding rights at workplace, support from company, other employee and family about breastfeeding behavior, explaining correlation between predisposing, enabling, and reinforcingfactors to working woman breastfeeding behavior; and also make concept to implement of breastfeeding right to working mother. This is an explanatory research with cross sectional approach, use quantitative and qualitative methods. Amount of samples are 74 mothers who hasbaby under two years old, at Kariadi Hospital and University of Dian Nuswantoro Semarang.Results : There is good predisposing and reinforcing factors in mother behavior, but bad in enabling factor. Statistic test with Pearson Product moment shows that predisposing and enabling factors are correlated to breastfeeding behavior (correlation coefficient of predisposing factor0.3, p-value 0.09 and correlation coefficient of enabling factor 0.241, p-value 0.038). Range Spearmen statistic test shows that reinforcing factors do not correlated to breastfeed behavior (p-value 0.73). From the report of focused group discussion with working mother, the researchersuggest to advocate and socialize the breastfeeding right, lactation management training for working mother, breastfeeding campaign, forming working mother forum in workplace, providing facilities for working mother to squeeze breast milk, that provided with cooler. The workplacealso have to give enough time (about 30 minutes, 2 times per day), to squeeze her breast milk.Keywords: breastfeeding, working mother, breastfeeding rights